I need to solve this by using the substitution method. Then graph.......please help. y=-x+1 2x-y=5

Subsititute in for 'y' in the second equation using the first: 2x - (-x + 1) = 5 2x + x + 1 = 5 3x + 1 = 5 3x = 5 - 1 3x = 4 x = 4/3

ok well u know what y equals..so plug in the answer for y! meaning u would plug this in.. 2x-(-x+1)=5

then you would solve from there!

ok thats what I got was x=4/3 but the book says (2,-1)

Did you try graphing the expressions?

no I don't know how

Your first equation is in y=mx + b format

oh ok I remember kinda how to do that......I will just have to look back in the book

Then turn your second equation to y= mx +b format too: 2x-y=5 -y = -2x + 5 y = 2x - 5

ok thanks

If you need help finding it, post once again and we can help you complete it

will do

Join our real-time social learning platform and learn together with your friends!